Analysis of Efforts to Increase Customer Loyalty in Improving Brand Trust, Marketing Communication Strategies and Product Diversity - Dedy Lazuardi (Jurnal Manajemen Bisnis Eka Prasetya, 2021)
This study aims to determine the effect of Brand Trust, Marketing Communication Strategies and Product Diversity on Customer Loyalty at PT. Jaya Abadi Chandra Kartika Medan. The population in this study are customers of PT. Jaya Abadi Chandra Kartika Medan totaling 137 respondents. The technique of determining the number of samples used in this study is Slovin formula and totaling 102 respondents. The results of the research analysis show that Brand Trust, Marketing Communication Strategies and Product Diversity partially have a positive and significant effect on Customer Loyalty at PT. Jaya Abadi Chandra Kartika Medan. The results showed that Brand Trust, Marketing Communication Strategies and Product Diversity simultaneously have a positive and significant effect on Customer Loyalty at PT. Jaya Abadi Chandra Kartika Medan. The results of this study are supported by the value of R square (R2) which means Brand Trust, Marketing Communication Strategies and Product Diversity have an effect on Customer Loyalty at PT. Jaya Abadi Chandra Kartika Medan. While the remaining is effected by other factors originating from outside this research model such as brand image, promotion, and location.